Improving Athlete Data Protection: Tackling Privacy and Economic Risks in Digital Security - Zhao Shuang; Guo Liya (Ilmu Inovasi Nusantara, 2024)
In the context of the rapid development of network information technology, the Internet has increasingly influenced various sectors, including sports. One critical issue that arises in sports is the leakage of athletes' personal information, which has become a prominent concern in network information security. Athlete data not only concerns their privacy but also holds significant economic value, making it vulnerable to exploitation. As a result, protecting athletes' data has become a pressing issue, with an urgent need to safeguard their independent rights and interests. This study aims to address the challenges surrounding the protection of athletes' information. Specifically, it seeks to investigate the inadequacies of traditional protection methods, which have operated mainly within personality and privacy rights frameworks. However, with the increasing commercialization of athletes' data and the growing recognition of its asset-like properties, these traditional approaches are no longer sufficient to ensure comprehensive protection. The study employs a literature review method and comparative analysis, focusing on various perspectives regarding athletes' information protection. The findings highlight the need to shift from the traditional legal frameworks towards a new system that considers athlete data's personal and economic dimensions. As a recommendation, the study strongly advocates for developing a more robust and multi-dimensional protection system, incorporating legal and financial measures to safeguard athletes' rights in the digital era